Optimization of Local Feed Ingredient Composition to Achieve 30% Protein Levels in Cultivated Fish Feed Production - Zebua, Ratna Dewi; Laoli, Destriman; Telaumbanua, Betzy Victor; Dawolo, Januari; Zebua, Okniel (Aquaculture Department, University of Mataram, 2025)
Aquaculture plays a vital role in meeting the global demand for animal protein, yet the dependency on expensive imported feed ingredients remains a significant challenge. Optimizing the use of local feed ingredients is a strategic approach to enhance sustainability and cost-efficiency in fish farming. This research aims to optimize the composition of local feed ingredients to achieve 30% protein content in farmed fish feed. The formulation involves rice bran, corn bran, fish meal, and tofu dregs, selected based on local availability and protein content. The methodology includes analysis of the protein content of raw materials, formulation testing, and physical evaluation of feed. The results show that the pellets produced have nutritional quality that meets the target, good physical stability, and cost efficiency of up to 40% compared to commercial feed. This research makes a significant contribution in supporting the sustainability of the fish farming industry and reducing dependence on imported raw materials.